Clinical Outcomes of Implants Placed in Extraction Sockets and Immediately Restored: A 7‐Year Single‐Cohort Prospective Study. (16th February 2016) - Barone, Antonio; Marconcini, Simone; Giammarinaro, Enrica; Mijiritsky, Eitan; Gelpi, Federico; Covani, Ugo
Abstract: Background: The placement of implants immediately after tooth extraction has proven to be a predictable treatment strategy with a very high success rate. Purpose: The aim of the present 7‐year prospective single cohort study was to evaluate the success rate, marginal bone level (MBL), soft tissue stability of implants placed in fresh extraction sockets and immediately restored. Material and Methods: This prospective cohort study included 37 implants in 32 patients (19 females and 13 males) with an average age of 40.1 ± 13.3 (range: 21–63 years) who received immediate implants and immediate single unit restorations. Outcome evaluations were: implant failures, complications, MBL, width of keratinized gingiva, facial soft tissue (FST) levels, modified Plaque Index and modified Bleeding Index. Results and Conclusions: The cumulative survival rate was of 94.6% at 7‐year visit. The mean MBL was −0.6 ± 0.49 mm at baseline and 1 ± 0.2 mm after 7 years. The FST Level was 0.4 ± 0.69 mm at baseline and 0.02 ± 0.70 mm at the 7‐year follow‐up. The Width of Keratinazed Gingiva was 3.8 ± 0.47 mm at baseline and 3.1 ± 0.42 mm at 7‐year follow‐up. Implants placed immediately after tooth extraction and immediately restored showed predictable clinical outcomes in this prospective study.